The possibility of regulating for obesity prevention – understanding regulation in the Commonwealth Government. Issue 3 (21st November 2012) - Crammond, B.; Van, C.; Allender, S.; Peeters, A.; Lawrence, M.; Sacks, G.; Mavoa, H.; Swinburn, B. A.; Loff, B.
Summary A complex regulatory package is likely to be necessary to effectively reduce obesity prevalence in developed countries. This study investigated the barriers and facilitators to implementing regulatory interventions to prevent obesity within the executive arm of the Australian Commonwealth Government. Policy reviews were conducted on nine government departments to understand their roles and interests in obesity. From this process we identified regulatory review carried out by the Office of Best Practice Regulation as possibly posing a barrier to law reform for obesity prevention, along with the complexity of the food policymaking structures. The policy reviews informed subsequent in‐depth semi‐structured interviews with senior Commonwealth government officers (n = 13) focused on refining our understanding of the barriers to enacting obesity prevention policy. In addition to the two barriers already identified, interviewees identified a lack of evidence for interventions, which would reduce obesity prevalence, and the influence of politicians on executive decisions as posing obstacles. Most interviewees believed that the barriers to regulating to prevent obesity were strong and that intervention by elected politicians would be the most likely method of implementing obesity prevention policy.